Impact of positive lymph nodes and RAI therapy on survival in N1b papillary thyroid carcinoma - Jian, Jie; Wei, Meng; Li, Xumei; Xiong, Qian; Xiang, Jiangming; Zhao, Shengping; Peng, Yuxi; Huang, Jingjing (Frontiers in Endocrinology, 2025)
BackgroundPatients with N1b papillary thyroid carcinoma (PTC) was associated with a worse prognosis. The prognostic role of positive lymph nodes (PLN) and whether postoperative radioactive iodine (RAI) therapy conferred a survival benefit were debatable issues in these patients.MethodsData were drawn from the SEER database for PTC patients with clinical N1b disease diagnosed between 2004-2015. All patient underwent total thyroidectomy with or without RAI. Patients were categorized by age (≥55 years and <55 years) and analyzed based on PLN. Propensity score matching (PSM) were used to balance characteristics between patients who did and did not receive RAI therapy. Overall survival (OS) was the primary outcome. Kaplan-Meier survival analysis and Cox analysis were performed.ResultsA total of 4343 N1b PTC patients were included, with 884 patients aged ≥55 years and 3459 patients aged <55 years. In patients aged ≥55 years, the optimal PLN cutoff for risk stratification was 8. Those with PLN ≥9 had significantly lower 5-year (83.7% vs. 90.1%), 10-year (67.4% vs. 78.8%) and 15-year (50.3% vs. 59.5%) OS rates. After adjusting, the hazard ratio for death in the PLN ≥9 group increased by 30%. After PSM, in subgroup of aged ≥55 years and PLN ≥9, the survival benefit was notable in those received RAI therapy. In contrast, for patients aged ≥55 years and PLN ≤8 or aged <55 years, no survival difference was found between those received RAI and those not.ConclusionsIn N1b PTC patients aged ≥55 years, PLN ≥9 predicted a poorer survival. Postoperative RAI therapy offered survival benefits for this subgroup.